Morning glories (2010), volume 1 ebook - Spencer, Nick (Morning Glories (2010), 2015)
Morning Glory Academy is one of the most prestigious prep schools in the country, but something sinister and deadly lurks behind its walls. When six gifted but troubled new students arrive, they find themselves trapped and fighting for their lives as the secrets of the academy reveal themselves!. Author: Nick Spencer. Illustrator: Joe Eisma, Rodin Esquejo . 2011 Nick Spencer & Joe Eisma.